The Virus–Host Interplay in Junín Mammarenavirus Infection - Giovanna Lucrecia Gallo; Nora López; María Eugenia Loureiro (Viruses, 2022)
Junín virus (JUNV) belongs to the Arenaviridae family and is the causative agent of Argentine hemorrhagic fever (AHF), a severe human disease endemic to agricultural areas in Argentina. At this moment, there are no effective antiviral therapeutics to battle pathogenic arenaviruses. Cumulative reports from recent years have widely provided information on cellular factors playing key roles during JUNV infection. In this review, we summarize research on host molecular determinants that intervene in the different stages of the viral life cycle: viral entry, replication, assembly and budding. Alongside, we describe JUNV tight interplay with the innate immune system. We also review the development of different reverse genetics systems and their use as tools to study JUNV biology and its close teamwork with the host. Elucidating relevant interactions of the virus with the host cell machinery is highly necessary to better understand the mechanistic basis beyond virus multiplication, disease pathogenesis and viral subversion of the immune response. Altogether, this knowledge becomes essential for identifying potential targets for the rational design of novel antiviral treatments to combat JUNV as well as other pathogenic arenaviruses.